The science of tender passion: attempts to codify love in the Ovidian tradition of the Middle Ages - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2020)
It is dedicated to the attempts made within the framework of the Ovidian Renaissance to create codes of practice that regulate and adjust human behavior in the space of love relationships. The features of love codes of the turn of the 12th–13th centuries are revealed.
Keywords: knightly etiquette; love code; law courts of love; rules of love correspondence; idea of an individual; inner world; woman as a subject